Study of management of diaphyseal fracture shaft femur by intramedullary interlocking nail - Tiwari, Ayush; Kohli, Sarabjeet Singh; Kokne, Manish (International Journal of Research in Orthopaedics, 2019)
Background: Aim of this study was to analyze the effectiveness of interlocking nail in management of femoral diaphyseal fractures with special reference to fracture anatomy, pattern and status of stability. Methods: This hospital based prospective study was done in the department of Orthopedics, MGM Medical College Navi Mumbai. A total of 41 patients who were admitted in our institute was included to evaluate management of diaphyseal fracture shaft femur by intramedullary interlocking nail from July 2015 to July 2017. They were asked to follow up at 6 weeks, 3 months and 6 months. Results: Most of the fractures (70.7%) were united in 16-20 weeks while 10 (24.4%) fractures were united in 10-15 weeks and 2 (4.9%) fractures were united in 21-25 weeks. The mean time to union was 16.87±3.09 weeks. In the present study, 26 out of 41 patients had excellent results (63.4%) with full, pain free, function of the extremity. 13 patients with good result (31.8%), 9 patients had flexion deformity 1200, 3 patients had shortening 2 cm, 2 patients had shortening 1 cm. Two patients with fair result (4.8%), both had flexion deformity and none had with poor result. So overall, we had 95.2% excellent to good and 4.8% fair results. Conclusions: Interlocking intramedullary nailing is the most effective ad successful method of definitive primary treatment, in most types of fractures of femur shaft. It provides strong fixation, rotational stability and earliest return to functional status, as rate of healing is good with nailing.